-5(2r-0.3)+0.4(4r+3)=-64

Simple and best practice solution for -5(2r-0.3)+0.4(4r+3)=-64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2r-0.3)+0.4(4r+3)=-64 equation:


Simplifying
-5(2r + -0.3) + 0.4(4r + 3) = -64

Reorder the terms:
-5(-0.3 + 2r) + 0.4(4r + 3) = -64
(-0.3 * -5 + 2r * -5) + 0.4(4r + 3) = -64
(1.5 + -10r) + 0.4(4r + 3) = -64

Reorder the terms:
1.5 + -10r + 0.4(3 + 4r) = -64
1.5 + -10r + (3 * 0.4 + 4r * 0.4) = -64
1.5 + -10r + (1.2 + 1.6r) = -64

Reorder the terms:
1.5 + 1.2 + -10r + 1.6r = -64

Combine like terms: 1.5 + 1.2 = 2.7
2.7 + -10r + 1.6r = -64

Combine like terms: -10r + 1.6r = -8.4r
2.7 + -8.4r = -64

Solving
2.7 + -8.4r = -64

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-2.7' to each side of the equation.
2.7 + -2.7 + -8.4r = -64 + -2.7

Combine like terms: 2.7 + -2.7 = 0.0
0.0 + -8.4r = -64 + -2.7
-8.4r = -64 + -2.7

Combine like terms: -64 + -2.7 = -66.7
-8.4r = -66.7

Divide each side by '-8.4'.
r = 7.94047619

Simplifying
r = 7.94047619

See similar equations:

| log(9x-8)=2 | | 3x-2=5+32 | | 20c=7 | | 26=6(-4f) | | 3k+45=-6x | | -6(x+2)-41=8-13 | | 4(3w+5/2)-3=5w | | 72x+300=72+450 | | 4x-4(2x-4)=-2(x-1) | | 2.50+14.75=x | | -2(3y-6)-y=-3(y-4) | | K+2*6=2.5 | | (7x+21)=7 | | 21x+8-24=1-5 | | .72x+3=.3(2.4+15) | | 75=-24+-9 | | 68=0.20(20x+50)+12 | | -(3y-4z+2)= | | -1-5(-8+6n)=-11(8+6n) | | 26x+6=5(5x+6) | | 6(z-3)+7z-2= | | 0.2x+5=0.3x+7 | | 5+7y=18 | | -1+a=1 | | 6(5-x)=12 | | 6+3(x-4)=5x-3(x+2) | | 4c-c=26 | | 4n-8=10-2b | | 2+6x-2x=6+2x-2x | | 3x+2y(3x-13)=19 | | 2(-3x^2+2x-1)= | | -18p-19p+17=p+17 |

Equations solver categories